Mathematical economics - Chichilnisky, Graciela (Cheltenham, UK ; Northampton, MA : E. Elgar Pub., 1998)
Mathematical Economics is an authoritative collection of the most influential contributions essential to an understanding of this important area of economic science. These seminar papers illustrate the development of the field from its inception in the 19th century up to the present, and exhibit the power of mathematics to lead to new thinking which can illuminate the scientific structures underlying economic arguments. Many of these papers started new fields of economics, influencing deeply the way economists think about their world. They illustrate the extensive range of topics to which mathematics has been applied productively, and show the areas of mathematics which have proved valuable, including functional analysis, linear algebra, algebraic and differential topology, stochastic processes and dynamical systems. They also show the extent to which todays policy analysis rests on yesterdays mathematical economics. Anyone with an interest in economics as a science will find this collection indispensable. The collection is an essential part of any course using mathematical economics.
Includes bibliographical references and indexes.
lje 21/01/14
Loan
Keywords: Economics, Mathematical